(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2022)
Upper Triassic (Rhaetian) foraminifera belonging to the species Glomospira charoides (Jones & Parker), Gaudryinopsis kelleri (Tappan), G. triadica (Kristan-Tollmann), Ammobaculites zlambachensis Kristan-Tollmann, Verneuilinoides racema (Trifonova), and Trochammina cf. jaunensis Brönnimann & Page were investigated using X-ray micro-computed tomography. Foraminifera were recovered from the drill core CM31 of the 817 Lebăda Vest borehole, located off the coast of Romania on the western Black Sea shelf, from depths of 2623 m to 2625 m. Tomographic data was used to generate digital models, which were then virtually sectioned in desirable ways. The acquired transects can be used for comparison with specimens viewed in thin sections, providing a better connection between specimens recovered from residues and those observed in thin sections using transmitted light microscopy.